Association Between Non-obstructive Chronic Bronchitis and Incident Chronic Obstructive Pulmonary Disease and All-Cause Mortality: A Systematic Review and Meta-Analysis - Wu, Fan; Fan, Huanhuan; Liu, Jing; Li, Haiqing; Zeng, Weifeng; Zheng, Silan; Tian, Heshen; Deng, Zhishan; Zheng, Youlan; Zhao, Ningning; Hu, Guoping; Zhou, Yumin; et al. (Frontiers in Medicine, 2022)
Abstract Background: Chronic bronchitis in patients with chronic obstructive pulmonary disease (COPD) is associated with poor respiratory health outcomes. However, controversy exists around whether non-obstructive chronic bronchitis (NOCB) is associated with airflow obstruction, lung function decline, and all-cause mortality in ever smoker or never smoker. Research Question: This systematic review and meta-analysis aimed to clarify the relationship between NOCB and incident COPD, lung function decline, and all-cause mortality, and to quantify the magnitude of these associations. Study Design and Methods: We searched PubMed, Embase, and Web of Science for studies published up to October 1, 2021. Eligibility screening, data extraction, and quality assessment of the retrieved articles were conducted independently by two reviewers. Studies were included if they were original articles comparing incident COPD, lung function decline, and all-cause mortality in normal spirometry with and without chronic bronchitis. The primary outcomes were incident COPD and all-cause mortality. The secondary outcomes were respiratory disease-related mortality and lung function decline. Pooled effect sizes and 95% confidence intervals (CIs) were calculated using the random-effects model. Results: We identified 17,323 related references and included 14 articles. Compared with individuals without NOCB, individuals with NOCB had an increased risk of incident COPD (odds ratio: 1.98, 95% CI: 1.21–3.22, I2=76.3% and relative risk: 1.44, 95%CI: 1.13–1.85, I2=56.1%), all-cause mortality (hazard ratio [HR]: 1.38, 95%CI: 1.26–1.51, I2=29.4%), and respiratory disease-related mortality (HR: 1.88, 95%CI: 1.37–2.59, I2=0.0%). Data on the decline in lung function could not be quantitatively synthesized, but the five articles that assessed the rate of decline in lung function showed that lung function declines faster in individuals with NOCB. The mean difference in the additional decline in forced expiratory volume in 1 second ranged from 3.6 to 23.2 mL/year. Interpretation: Individuals with NOCB are at a higher risk of incident COPD and all-cause mortality than individuals without NOCB, highlighting the crucial need for strategies to screen for and reduce NOCB risk. PROSPERO registration number: CRD42020202837